2005
DOI: 10.1128/jvi.79.1.326-340.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role for Tumor Necrosis Factor Alpha in Murine Cytomegalovirus Transcriptional Reactivation in Latently Infected Lungs

Abstract: Interstitial pneumonia is a major clinical manifestation of primary or recurrent cytomegalovirus (CMV) infection in immunocompromised recipients of a bone marrow transplant. In a murine model, lungs were identified as a prominent site of CMV latency and recurrence. Pulmonary latency of murine CMV is characterized by high viral genome burden and a low incidence of variegated immediate-early (IE) gene expression, reflecting a sporadic activity of the major IE promoters (MIEPs) and enhancer. The enhancer-flanking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
111
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 61 publications
3
111
1
Order By: Relevance
“…TNF expression is upregulated by allogeneic transplantation (Fig. 6 andHummel et al, 2009, 2001) and TNF is sufficient to activate MCMV IE gene expression and/or reactivation in vivo (Cook et al, 2006;Hummel et al, 2001;Simon et al, 2005). However, our previous studies showed that TNF was not required for reactivation of IE gene expression in response to allogeneic transplantation .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…TNF expression is upregulated by allogeneic transplantation (Fig. 6 andHummel et al, 2009, 2001) and TNF is sufficient to activate MCMV IE gene expression and/or reactivation in vivo (Cook et al, 2006;Hummel et al, 2001;Simon et al, 2005). However, our previous studies showed that TNF was not required for reactivation of IE gene expression in response to allogeneic transplantation .…”
Section: Discussionmentioning
confidence: 78%
“…CMV genomes are heterochromatinized and the IE genes, which are required for lytic replication, are transcriptionally silent in latent infection (Grzimek et al, 2001;Hummel et al, 2001;Kurz et al, 1997Kurz et al, , 1999Liu et al, 2008Liu et al, , 2010Seckert et al, 2013;Simon et al, 2005). Activation of IE gene expression, through recruitment of transcription factors that control MIEP activity and remodelling of viral chromatin, is therefore likely required for reactivation of the virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous in vitro and in vivo studies have elucidated the mechanisms of CMV reactivation and have shown that cytokine production, in particular tumor necrosis factor ␣ (TNF-␣), is involved in reactivation. [27][28][29] Although the molecular mechanism of HHV-6 reactivation remains unclear, we recently showed that interleukin-6 (IL-6) and TNF-␣ might play an important role in HHV-6 reactivation in patients with severe druginduced hypersensitivity syndrome. 30 These findings also suggest that cytokines may play an important role in HHV-6 reactivation in patients after organ transplant.…”
mentioning
confidence: 99%
“…Different mechanisms of CMV-induced vascular or tissue damage in chronic allograft dysfunction have been proposed. The systemic inflammation induced by CMV replication might alter the state of allograft tolerance in the transplant recipient and subsequently trigger acute allograft rejection mediated by cytokines and other chemical mediators (39,40), which in turn will increase the risk for chronic allograft dysfunction.…”
Section: Viral Infections and Chronic Allograft Dysfunctionmentioning
confidence: 99%